2013
DOI: 10.1080/00223131.2013.773159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma-ray irradiation on the deoxygenation of salt-containing water using hydrazine

Abstract: In spent fuel pools at the Fukushima Daiichi nuclear power plant, hydrazine was added to salt-containing water in order to reduce dissolved oxygen. Hydrazine is known to reduce dissolved oxygen in hightemperature pure water, but its deoxygenation behavior in salt-containing water at ambient temperature in the presence of radiation is unknown. Deoxygenation using hydrazine in salt-containing water was thus investigated using a 60 Co gamma-ray source and artificial seawater at room temperature. Water samples con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…•+ , • N 2 H 3 , and NH 3 are formed after the reactions shown in Equations ( 13) and (14). Among these products, N 2 H 4…”
Section: Radiolysis Of Hydrazine In Acidic Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…•+ , • N 2 H 3 , and NH 3 are formed after the reactions shown in Equations ( 13) and (14). Among these products, N 2 H 4…”
Section: Radiolysis Of Hydrazine In Acidic Solutionmentioning
confidence: 99%
“…They concluded that N 2 H 4 exists mainly as N 2 H 5 + or N 2 H 6 2+ in the acidic solution, both of which cause rapid consumption of NO 3 ● radicals. Motooka et al also reported that the deoxygenation reaction with radiolysis of N 2 H 4 can be suppressed by salt in the water in the γ-radiation field [ 14 ]. In this way, the molecular structure of N 2 H 4 after radiolysis and the decomposition mechanism of the N 2 H 4 depend on the composition of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we detected H 2 O 2 in artificial seawater irradiated by gammaray (8). To evaluate the oxidation power of H 2 O 2 , we obtained cathodic polarization curves of platinum in the artificial seawater with and without H 2 O 2 at room temperature.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…In our previous study, H 2 O 2 at a level of a few ppm was detected in the ASW after gamma-ray irradiation for 1 h [11]. In order to evaluate the oxidation power of H 2 O 2 , cathodic polarization curves of platinum in the ASW with and without H 2 O 2 at room temperature were measured and analyzed.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%